ESTETIKA DAN ETIKA TARI GUEL PADA MASYARAKAT GAYO KABUPATEN ACEH TENGAH - Saadah Saadah Saadah (Universitas Negeri Medan, 2013)
This study aims to determine the aesthetics , ethics , presentation form , motion , fashion , music accompaniment, lyrics dance Guel in Central Aceh district of Gayo society. In the discussion of this study , used theories who related research topics , such as the form of presentation of theory , aesthetic theory and the theory of ethics . Time is used to discuss research on the public Guel Dance Central Aceh Gayo conducted for 3 months ie from June to early August 2013 . Where the research is in the district of Central Aceh district Bebesen . The population in this study is the Gayo , Guel Dance Artists , Artists music, society as a party organizer , dance Guel, Guel the actors dance dance dancers and musicians and connoisseurs of dance Guel Guel . Data was collected by the method of field work which includes several aspects , namely : Literature study , observation , interviews, and documentation , and then were analyzed by descriptive qualitative method . Based on research conducted in the District Bebesen Central Aceh district . Guel Dance originated from Central Aceh and Gayo society is a traditional dance , this dance is not known who the creator , when it was created and where it was created . Guel Dance is a dance reception at the marriage ceremony Gayo society . Guel dance presentation ceremony held at the Mah Bai . The purpose of this dance is to include a reception in honor of the groom's entourage who came with his family and relatives . Guel dancers dance number consists of 1-4 male dancers and female dancers 6-10 . This dance contains elements of aesthetics ( beauty ) which can be seen in motion , clothing , musical , and dance accompanist poem Guel . Guel dance aesthetic is not only observed in terms of beauty , but also observed in terms of quality contained in the Guel dance . In addition there are also ethical aesthetics in dance Guel , we can see in motion , clothing and dance accompanist poem Guel , all have appropriate rules and norms of Islamic Sharia laws in force at the Gayo people in Central Aceh district .